2012
DOI: 10.1007/s10144-012-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of dispersal and control methods for the riverine tsetse fly Glossinapalpalisgambiensis (Diptera: Glossinidae): a modelling study

Abstract: We used a spatial model of a riverine tsetse fly species Glossina palpalisgambiensis life cycle to investigate the interaction between their dispersal and three control methods and to document these interactions using sensitivity analyses. The model is currently limited to gallery forest habitat inhabited by Glossina palpalisgambiensis in the dry season in the sub‐humid zone of West Africa. The control methods modelled were traps and targets (TT), insecticide‐treated livestock (ITL), and the sterile insect tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…This entomological method nevertheless presents a number of important limitations, namely low sensitivities or efficiencies, as it was shown that only 20% of the traps attracted flies are actually captured [10], [11]. In addition it has been suggested that traps become less efficient when tsetse densities decrease [12] possibly due to density-dependant dispersal [13]. They may thus lead to an underestimation of the true densities.…”
Section: Introductionmentioning
confidence: 99%
“…This entomological method nevertheless presents a number of important limitations, namely low sensitivities or efficiencies, as it was shown that only 20% of the traps attracted flies are actually captured [10], [11]. In addition it has been suggested that traps become less efficient when tsetse densities decrease [12] possibly due to density-dependant dispersal [13]. They may thus lead to an underestimation of the true densities.…”
Section: Introductionmentioning
confidence: 99%
“…The short dispersal distances during these seasons indicate that the weevils are likely to be clumped on plants relatively close to their release point, which results in an aggregated distribution of this species in the field (Yasuda, ). This behaviour would require careful consideration when planning an eradication programme because clumping would reduce the success of an eradication using SIT (Barclay & Vreysen, ).…”
Section: Discussionmentioning
confidence: 99%
“…They recommended that the interpretation of contours incorporate environmental variables, especially wind currents. Barclay and Vreysen (2013) used area of attraction for the riverine tsetse (Glossina palpalis gambiensis (Vanderplank)) that was equivalent to Wall and Perry's range of attraction but explicitly included dispersal, effectively converting the measure to sampling range. These authors found that trapping efficiency (percentage of the population within the area of attraction that was trapped each day) increased with dispersal distance and percent of flies dispersing each day.…”
Section: Modelling Components Of Trap Attractivenessmentioning
confidence: 99%